2006
DOI: 10.1515/hf.2006.069
|View full text |Cite
|
Sign up to set email alerts
|

Polycarboxylic acids as non-formaldehyde anti-swelling agents for wood

Abstract: Wood specimens of fir (Abies alba Mill) and beech (Fagus sylvatica L.) were chemically modified using polycarboxylic acids (PCA), cured by convection heating or microwave treatment and analyzed by HPLC. A new non-formaldehyde cross-linking system was composed of citric acid (CA) and 1,2,3,4-butanetetracarboxylic acid (BTCA), which are representative polycarboxylic acids (PCAs). These reagents require phosphono-based catalysts, so a sodium hypophosphite (SHP) catalyst was used in this study. The effects of PCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 12 publications
0
33
0
1
Order By: Relevance
“…In the case of beech wood, the average increase of compression strength also occurred due to wood modifi cation, but the increase was insignifi cant ( Figure 3, Table 2). The amount of CA bound to wood is signifi cantly larger in fi r wood (Katović et al, 2006). Higher average compression strength of modifi ed fi r wood can be explained by better crosslinking of CA and wood.…”
Section: Rezultati I Diskusijamentioning
confidence: 99%
“…In the case of beech wood, the average increase of compression strength also occurred due to wood modifi cation, but the increase was insignifi cant ( Figure 3, Table 2). The amount of CA bound to wood is signifi cantly larger in fi r wood (Katović et al, 2006). Higher average compression strength of modifi ed fi r wood can be explained by better crosslinking of CA and wood.…”
Section: Rezultati I Diskusijamentioning
confidence: 99%
“…To resolve these serious problems, some studies about binderless (Gao et al 2011) or natural adhesives, such as citric acid and sucrose, have been conducted. Citric acid is an organic polycarboxylic acid, which contains three carboxyl groups and has been considered as a cross-linking agent for wood (Vukusic et al 2006) and plant fiber.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that citric acid-bonded boards exhibit high mechanical properties and good dimensional stability. In addition, citric acid has also been studied as a cross-linking agent for wood (Vukusic et al 2006;Hasan et al 2007), starch (Reddy and Yang 2010), and as an absorber for heavy metal ions (Thanh and Nhung 2009). Studies have shown that when citric acid is used as a cross-linking chemical, it reacts with the hydroxyl groups and reduces the hygroscopicity of wood as well as the tendency of wood to swell or shrink (Rowell 1991;Vukusic et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, citric acid has also been studied as a cross-linking agent for wood (Vukusic et al 2006;Hasan et al 2007), starch (Reddy and Yang 2010), and as an absorber for heavy metal ions (Thanh and Nhung 2009). Studies have shown that when citric acid is used as a cross-linking chemical, it reacts with the hydroxyl groups and reduces the hygroscopicity of wood as well as the tendency of wood to swell or shrink (Rowell 1991;Vukusic et al 2006). Umemura et al (2012) pointed out that ester linkages can be detected by Fourier transform infrared spectroscopy (FTIR), which indicates that the carboxyl groups from citric acid can react with hydroxyl groups from wood, improving the performance of boards.…”
Section: Introductionmentioning
confidence: 99%